PENERAPAN ENERGI MATAHARI DALAM MENDUKUNG SISTEM KOLAM PETERNAKAN IKAN MAS HIAS JAMAL SSFARM - Hidayaturrohman, Qisthi Alhazmi; Lukmana, Muhammad Arifudin; Fahrudin, Fahrudin; Fauzi, Ade Fikri (Universitas Kadiri, 2021)
Solar radiation could be used as alternative energy by using solar panel as a transducer to convert solar radiation energy to electricity energy. Jamal SSFarm, a family-owned business in decorative fish cultivation had problem in electricity energy limitation for their operational works. Researcher and team offered solutions to install and implement solar energy as an alternative energy by using solar panels. This community service works have done by two steps, the first step was surveying and buying stuffs and the second step was installment and testing at the partner location. In our activities, the alternative energy system works well. The testing device showed 1.25 ampere of its current, which shows that the device works well. That matter are in line with our partner expectation.